Investigating the Relationship Between Leg Strength and Running Kinematics in Healthy Novice Runners - Sciberras, Chanelle (2024)
INTRODUCTION. Muscle weakness and biomechanical alterations have been recognized as risk factors for various running-related injuries (RRIs), fuelling a growing interest in understanding the relationship between strength and running biomechanics. While existing research has predominantly focused on the relationship between hip strength and kinematics, other potential associations remain largely unexplored. Moreover, many studies have employed isometric strength testing, which may not accurately reflect muscle function during running. Notably, there is a lack of research on novice runners, despite their heightened susceptibility to RRIs. Consequently, the purpose of this thesis is to investigate the association between lower-limb isokinetic strength and running kinematics in healthy novice runners. METHODS. 10 male and 10 female novice runners participated in this study. 3D running kinematic data was collected using a marker-based motion capture system (Vicon). Peak isokinetic strength of the hip abductors and adductors, knee flexors and extensors, as well as the ankle plantarflexors, dorsiflexors, invertors and evertors was measured using an isokinetic dynamometer (Biodex System 4 Pro). Spearman correlation coefficients were used to determine the relationship between lower-limb isokinetic strength and stance phase running kinematics. RESULTS. Isokinetic hip abductor strength was significantly correlated to frontal plane hip kinematics in male novice runners (toe-off angle: r = -0.620, p = 0.004; minimum angle: r = -0.624, p = 0.003), but no such correlations were found in females. Overall, the findings do not support the notion that isokinetic hip abduction strength is correlated with knee kinematics in healthy novice runners. Hip adduction strength was associated with several frontal plane ankle kinematics in both male (initial contact angle: r = - 0.650, p = 0.002; toe-off angle: r = -0.534, p = 0.015; maximum angle: r = -0.546, p = 0.013; minimum angle: r = -0.710, p =< 0.001) and female novice runners (toe-off angle: r = -0.710, p = <0.001; minimum angle: r = -0.517, p = 0.020; range of motion (ROM): r = 0.579; p = 0.007). Additionally, knee flexion strength was associated with greater knee adduction in the male runners (initial contact angle: r = 0.486, p = 0.030; toe-off angle: r = 0.571, p = 0.008; maximum angle: r = 0.564, p = 0.010; minimum angle: r = 0.459, p = 0.042), as well as a larger peak knee flexion angle (r = 0.617, p = 0.004) and increased sagittal plane ankle ROM (r = 0.465, p = 0.039) in the female runners. Furthermore, concentric ankle strength exhibited several significant correlations with running kinematics at the hip, knee and ankle in novice runners. DISCUSSION. Male and female novice runners displayed distinct associations between lower-limb strength and running kinematics. Several significant correlations were identified between lower-limb isokinetic strength and injury-related kinematic parameters. Additionally, the findings suggest that strengthening the muscles of the foot and ankle, which has been shown to reduce RRIs, may also impact joint mechanics higher up the kinematic chain. Further research is needed to validate these results and assess the efficacy of lower-limb strengthening in altering running kinematics and mitigating the risk of RRIs.